Analysis Of Student Conceptual Errors And Procedural Errors In Solving Mathematical Problems - Syahrir, Syahrir; Fauzi, Azra; Juliawan, Rizcky; Lapele, Dina Amalya (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to analyze conceptual and procedural errors in solving mathematical problems. This research is a descriptive qualitative research that aims to explore mathematical misconceptions in students and their views on the misconceptions they experience. The misconceptions in this study were obtained from the results of tests and interviews. Misconceptions are most common in geometric materials, but they are not significantly different from other materials. Students still have difficulty due to lack of conceptual understanding of the problem or difficulty connecting mathematical concepts. The type of misconception that is most often experienced by students is confusion because they do not master the supporting concepts. The misconception that is most rarely experienced by students is the wrong classification of concept examples